EFFECTIVENESS OF BREASTFEEDING WITH HYPNOPRESSURE ON EARLY LACTATION IN COMMUNITY HEALTH CENTRES - Adevia Maulidya Chikmah; Istiqomah Dwi Andari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Tegal City Mayor Regulation No. 82 of 2023 concerning Behavioral and Social Change Strategies in Accelerating Stunting Reduction in Tegal City, explains that the target coverage of Exclusive Breastfeeding is 68% by 2024. The failure of the implementation of Exclusive Breastfeeding often occurs because the mother's breast milk has not come out in the early period after delivery, this is the reason for the mother to provide formula milk. Several risk factors that can slow the onset of lactation are anxiety, nutritional status, age, parity, type of delivery, birth weight, and early initiation of breastfeeding. Hypnopressure is a relaxation technique to help smooth the breastfeeding process. How to insert positive affirmations that help the breastfeeding process when the mother is relaxed or very concentrated on something. The purpose of this study is to Analyze the effectiveness of the implementation of breastfeeding with hypnopressure on lactation onset in the Tegal City Community Health Center Area. The research method used was pre-experimental, with a control group and intervention. The sampling technique was accidental sampling with 40 respondents. The results of the Mann Whitney test show that the asymp.sig value (2-tailed) is 0.004, which is smaller than the probability value of 0.05. Therefore, it can be concluded that